Critical Thinking Ability Test Instrument Design with Validity Test Pearson Correlation - Nursichati, Nursichati; Susongko, Purwo; Mulyono, Tri (Journal of English Language and Education, 2025)
This study aims to develop a valid test instrument model to measure critical thinking skills as an achievement of the Pancasila learner profile at the end of phase D. In developing this instrument, researchers used a validity test approach with the Pearson correlation method to ensure that each item can accurately reflect the understanding and ability of learners to process information objectively, build links between various information, analyze, evaluate and conclude. Data obtained from instrument testing involves learner responses which are then analyzed. The results of the analysis showed that all items had significant correlation coefficients, with values above the specified threshold, so they were declared valid. The validity of this instrument is very important to ensure that the evaluation of learning outcomes is in accordance with the standards set by the Merdeka Curriculum, and supports the achievement of curriculum goals in improving the quality of P5 results in schools. This research is expected to make a positive contribution to the development of more effective and efficient educational assessments.